Emission Problems of Vehicles and Advanced Fuels Application - Tarbajovský Pavol; Šoltésová Marieta; Puškár Michal (Journal of Mechanical Engineering, 2022)
The automotive industry is exposed to continued pressures, the goal of which is decarbonisation together with application of the advanced technologies and fuels, as well as utilization of the alternative vehicle drives. The main task of the scientific publication was a complex emission analysis of the selected vehicles during various test cycles, as well as a comparison of the individual emissions when using different types of fuel.